Flooring material and construction method
By combining a hollow gel gypsum self-leveling layer and an insulation layer, and adding components such as superabsorbent resin and hollow microspheres, the problems of high viscosity and poor fluidity of gypsum-based insulation mortar are solved, achieving precise leveling and excellent thermal insulation effect of floor insulation materials.
Patent Information
- Application Number
- CN202310925571.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2043-07-26
AI Technical Summary
Existing gypsum-based thermal insulation mortar has high viscosity and poor fluidity, making it impossible to achieve precise leveling and causing inconvenience in construction.
The structure adopts a combination of hollow gel gypsum self-leveling layer, hollow gel gypsum insulation layer and interface layer. It uses hollow gel gypsum insulation base material and foaming agent, and adds super absorbent resin, hollow microspheres and other components to form a stable hollow structure and heat insulation network.
It improves the fluidity and construction efficiency of thermal insulation materials, achieves precise leveling, reduces production costs, and enhances thermal insulation performance and material strength.
Smart Images

Figure CN116838054B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of indoor building floor insulation materials, in particular to a floor insulation material and a construction method. BACKGROUND
[0002] The insulation and leveling of building floors are important supporting materials for building energy saving. Traditional building floor insulation includes board materials and cement mortar, etc. The board material insulation system has low density and strength, and needs a protective layer of mortar on it to meet the delivery requirements. Moreover, the density difference between the insulation layer and the protective layer is large, and there are problems of "empty response" and cracking. The cement mortar insulation mortar has a large shrinkage in the later period, and generally has cracking. Gypsum is a green and energy-saving inorganic cementitious material, which has been applied in the building field in recent years. The application of gypsum can also promote the consumption and treatment of industrial waste residues. The existing gypsum-based insulation mortar has high viscosity and poor fluidity when applied to the floor system, which cannot achieve precise leveling, resulting in inconvenient construction and restricting the application of the product in the floor. SUMMARY
[0003] In view of the above problems in the prior art, the purpose of the present application is to provide a floor insulation material and a construction method to solve the problem of high viscosity and poor fluidity of gypsum-based insulation mortar in the prior art, which cannot achieve precise leveling.
[0004] To solve the above technical problems, the present application provides a floor insulation material, which is made of hollow gel gypsum self-leveling layer, hollow gel gypsum insulation layer and interface layer from top to bottom along the vertical direction; the interface layer is made of hollow gel gypsum insulation base material; the hollow gel gypsum insulation layer is made of hollow gel gypsum insulation base material and foaming agent; and the hollow gel gypsum self-leveling layer is made of hollow gel gypsum self-leveling material.
[0005] The hollow gel gypsum insulation base material comprises the following components by weight fraction: 80-90 parts of gypsum powder, 1-3 parts of superabsorbent resin, 0.1-0.2 parts of water reducing agent, 4-5.7 parts of hollow microspheres, 0.5-1 parts of silica fume and 0.05-0.1 parts of modifier; and the hollow gel gypsum self-leveling material comprises the following components by weight fraction: 65-75 parts of gypsum powder, 0.2-0.3 parts of water reducing agent, 4-8 parts of hollow microspheres, 0.03-0.05 parts of welan gum, 0.03-0.05 parts of cellulose ether, 0.02-0.05 parts of modifier, 0.03-0.05 parts of defoaming agent, 0.5-1.5 parts of metakaolin, 5-8 parts of cement and 7-25.19 parts of heavy calcium.
[0006] Preferably, the hollow gel gypsum heat preservation base material further comprises 0-14.35 parts of light calcium, wherein the light calcium is light calcium carbonate with fineness of 300-400 mesh.
[0007] Preferably, the gypsum powder is beta-type hemihydrate gypsum; the water reducing agent is modified polycarboxylic acid water reducing agent; the modifier is one or both of sodium gluconate and lactose; and the hollow microspheres are one or both of hollow glass beads and expanded microspheres.
[0008] Preferably, in the hollow gel gypsum heat preservation base material, the hollow microspheres have fineness of 200-300 mesh; and in the hollow gel gypsum self-leveling material, the hollow microspheres have fineness of 60-80 mesh.
[0009] Preferably, the superabsorbent resin is one or both of starch grafted acrylamide and crosslinked carboxymethyl cellulose grafted acrylamide; and the superabsorbent resin has fineness of 600-800 mesh.
[0010] Preferably, the xanthan gum has fineness of 300-400 mesh; and the cellulose ether has viscosity of 1000-2000 mpa·s.
[0011] Preferably, the metakaolin has fineness of 1000-1500 mesh; the cement is P·O42.5; and the heavy calcium is heavy calcium carbonate with fineness of 200-300 mesh.
[0012] Preferably, the foaming agent comprises the following components in parts by weight: 20-40 parts of tea saponin, 4-8 parts of polyvinyl alcohol, 5-10 parts of acrylic acid emulsion and 42-71 parts of water.
[0013] Preferably, the polyvinyl alcohol has fineness of 160-200 mesh; and the acrylic acid emulsion has glass transition temperature of 5-10℃.
[0014] The application further provides a construction method of the floor heat preservation material.
[0015] Step 1: Sprinkle water on the surface to be constructed to wet the surface and make the surface saturated with water;
[0016] Step 2: When the surface to be constructed leaves a small amount of liquid water, the hollow gel gypsum thermal insulation base material is dry scattered, and the hollow gel gypsum thermal insulation base material is rubbed into a slurry with a brush, and then the ground is interface treated to form an interface layer;
[0017] Step 3: The foaming agent is diluted with water and made into foam with a foaming machine for standby; wherein the amount of water is 40 times the amount of foaming agent;
[0018] Step 4: Water is added to the mixer, and then the hollow gel gypsum thermal insulation base material is added and stirred uniformly, and then the foam is injected and stirred to obtain a hollow gel gypsum thermal insulation slurry; wherein the amount of water is 70% of the mass of the hollow gel gypsum thermal insulation base material, and the volume of the foam is 0.5-0.8 times the volume of the slurry.
[0019] Step 5: The hollow gel gypsum thermal insulation slurry obtained in step 4 is poured on the surface of the interface layer and poured to the required thickness, and after hardening, a hollow gel gypsum thermal insulation layer is formed;
[0020] Step 6: After the hollow gel gypsum thermal insulation layer is completed for 24 hours, the self-leveling slurry made of self-leveling material is poured on the hollow gel gypsum thermal insulation layer, and is troweled to the required thickness to form a hollow gel gypsum self-leveling layer.
[0021] Preferably, before construction, the hollow gel gypsum thermal insulation base material of the present application is prepared, and the specific steps are as follows:
[0022] The gypsum powder and the modifier are added to the mixer, and high-speed stirring is carried out at 500-1000 rpm for 5 minutes, and then the superabsorbent resin, the water reducing agent, the hollow glass beads, the silica fume and the light calcium are added to the mixer, and slow stirring is carried out at 30-50 rpm for 20 minutes until uniform.
[0023] Preferably, before construction, the foaming agent of the present application is prepared, and the specific steps are as follows:
[0024] Water is added to the high-speed dispersion mixer, and then polyvinyl alcohol is added, and high-speed stirring is carried out at 800-1000 rpm for 120 minutes, and then the speed is adjusted to 300-400 rpm, and tea saponin is added and stirred for 60 minutes. Acrylic emulsion is added and stirred for 30 minutes, and then a foaming machine is used to make foam for standby.
[0025] Compared with the prior art, the present application has the following beneficial effects:
[0026] 1、the gypsum-based thermal insulation mortar is studied deeply in the present application, it is found that the water absorption resin can form saturated resin after absorbing water, which can play a good ball effect in the gypsum-based thermal insulation mortar, and improve the fluidity of the slurry; at the same time, the hollow microsphere can form a stable hollow structure in the thermal insulation layer, and improve the heat insulation effect, and the saturated resin after absorbing water can form a plurality of heat insulation cavities in the water absorption resin after evaporation of water in the saturated resin after hardening and drying, which can further improve the heat insulation effect of the material.
[0027] 2、the thermal insulation material has good fluidity during construction, can achieve accurate leveling, greatly shortens the construction time, and reduces the construction operation; at the same time, the foam is used as a light thermal insulation material, which can further reduce the production cost while ensuring the improvement of the thermal insulation effect, and has good application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 the structure diagram of the floor thermal insulation material of the present application.
[0029] In the figure: 1 is a hollow gel gypsum self-leveling layer, 2 is a hollow gel gypsum thermal insulation layer, 3 is an interface layer, and 4 is a concrete floor. DETAILED DESCRIPTION
[0030] The present application will be further described below in combination with the drawings and examples.
[0031] I. Examples and comparative examples
[0032] Example 1
[0033] The hollow gel gypsum thermal insulation base material is composed of 80 parts of gypsum powder, 1.5 parts of superabsorbent resin, 0.1 part of water reducing agent, 5.5 parts of hollow glass beads, 0.6 parts of silica ash, 0.05 parts of modifier, and 12.25 parts of light calcium.
[0034] The hollow gel gypsum thermal insulation foaming agent is composed of 25 parts of tea saponin, 4.5 parts of polyvinyl alcohol, 6 parts of acrylic acid emulsion, and 64.5 parts of water.
[0035] The hollow gel gypsum self-leveling layer is composed of 65 parts of gypsum powder, 0.2 parts of water reducing agent, 7 parts of hollow glass beads, 0.03 parts of Wali glue, 0.04 parts of cellulose ether, 0.02 parts of modifier, 0.04 parts of defoaming agent, 1.0 parts of metakaolin, 5 parts of cement, and 21.67 parts of heavy calcium.
[0036] Before construction, the hollow gel gypsum thermal insulation base material used in this embodiment is prepared, and the specific steps are as follows: the gypsum powder and the modifier are added to a blender, and high-speed stirring is performed at 500-1000 r / min for 5 min, then the superabsorbent resin, the water reducing agent, the hollow glass bead, the silica fume and the light calcium are added to the blender, and slow stirring is performed at 30-50 r / min for 20 min until uniform, and then the hollow gel gypsum thermal insulation base material is prepared.
[0037] The foaming agent used in this embodiment is prepared, and the specific steps are as follows: water is added to a high-speed dispersion blender, then polyvinyl alcohol is added, high-speed stirring is performed at 800-1000 r / min for 120 min, then the speed is adjusted to 300-400 r / min, tea saponin is added and stirred for 60 min. Acrylic emulsion is added and stirred for 30 min, and then a foam is prepared with a foaming machine and is ready for use.
[0038] The hollow gel gypsum self-leveling slurry used in this embodiment is prepared, and the specific steps are as follows: water is added to a blender, then the hollow gel gypsum self-leveling material is added, and stirring is performed for 60 s until uniform to obtain the hollow gel gypsum self-leveling slurry. The amount of water added is 45% of the mass of the hollow gel gypsum self-leveling material.
[0039] The specific construction steps are as follows:
[0040] Step 1: The surface to be constructed is sprinkled with water to wet the surface and make the surface saturated with water; the ground is wet and there is no obvious water body.
[0041] Step 2: When there is a small amount of liquid water on the surface to be constructed, the hollow gel gypsum thermal insulation base material is dry-sprinkled, and the hollow gel gypsum thermal insulation base material is rubbed into a slurry with a brush, and then the ground is interface treated to form an interface layer.
[0042] Step 3: The foaming agent is diluted with water, and a foam is prepared with a foaming machine and is ready for use; the amount of water used is 40 times the amount of the foaming agent.
[0043] Step 4: Water is added to a blender, then the hollow gel gypsum thermal insulation base material is added and stirred until uniform, then the foam is injected, and stirring is continued for 60 s to obtain the hollow gel gypsum thermal insulation slurry; the amount of water added is 70% of the mass of the hollow gel gypsum thermal insulation base material, and the volume of the foam is 0.5 times the volume of the slurry.
[0044] Step 5: The hollow gel gypsum thermal insulation slurry obtained in step 4 is poured onto the surface of the interface layer, and is poured to the required thickness, and after hardening, a hollow gel gypsum thermal insulation layer is formed.
[0045] Step 6: After the hollow gel gypsum insulation layer is completed for 24 hours, the self-leveling slurry made of the self-leveling material is poured on the hollow gel gypsum insulation layer, and the self-leveling layer is formed by batch scraping to the required thickness, and finally the floor and ground insulation material of the application is formed, and the structure is as shown in Figure 1 .
[0046] Example 2
[0047] The hollow gel gypsum insulation base material is composed of 90 parts of gypsum powder, 2.5 parts of superabsorbent resin, 0.15 parts of water reducing agent, 4.5 parts of hollow glass beads, 0.8 parts of silica fume, 0.1 parts of modifier, and 1.95 parts of light calcium.
[0048] The hollow gel gypsum insulation foaming agent is composed of 35 parts of tea saponin, 6 parts of polyvinyl alcohol, 10 parts of acrylic emulsion, and 49 parts of water.
[0049] The hollow gel gypsum self-leveling material is composed of 70 parts of gypsum powder, 0.25 parts of water reducing agent, 6 parts of expanded microspheres, 0.04 parts of Wali glue, 0.03 parts of cellulose ether, 0.026 parts of modifier, 0.05 parts of defoaming agent, 0.5 parts of metakaolin, 6 parts of cement, and 17.104 parts of heavy calcium.
[0050] The construction method of Example 2 is completely consistent with Example 1.
[0051] Example 3
[0052] Based on Example 1, the difference is that the amount of superabsorbent resin in the hollow gel gypsum insulation base material is 3 parts.
[0053] Example 4
[0054] Based on Example 2, the difference is that the amount of acrylic emulsion in the foaming agent in the hollow gel gypsum insulation layer is 5 parts.
[0055] Example 5
[0056] Based on Example 2, the difference is that the amount of expanded microspheres in the hollow gel gypsum self-leveling material is 4 parts.
[0057] Comparative Example 1
[0058] Based on Example 1, the difference is that the amount of superabsorbent resin is 0.5 parts.
[0059] Comparative Example 2
[0060] Based on Example 1, the difference is that the amount of hollow microbeads in the insulation base material and the self-leveling material is 10 parts.
[0061] Comparative Example 3
[0062] On the basis of example 1, the difference is that the high water absorption resin is 10 parts.
[0063] Comparative example 4
[0064] On the basis of example 1, the difference is that the hollow microsphere content in the thermal insulation base and the self-leveling material is 3 parts.
[0065] Comparative example 5
[0066] On the basis of example 1, the difference is that the hollow glass bead content in the hollow gel gypsum thermal insulation base is 1.5 parts.
[0067] II. Performance comparison
[0068] The performance of the examples and comparative examples is detected by GB / T 20473-2021 "Building thermal insulation mortar" and JC / T 1023-2021 "Gypsum-based self-leveling mortar" detection method. Considering that the thermal insulation material of the present application is multi-layer, the hollow gel gypsum thermal insulation material, hollow gel gypsum self-leveling and the whole thermal insulation material are detected respectively.
[0069] Table 1
[0070]
[0071]
[0072] From table 1, it can be seen that:
[0073] (1) From example 1 and comparative example 1, comparative example 3, it can be seen that the amount of high water absorption resin has a great influence on the dry density, compressive strength and thermal conductivity of the thermal insulation material: the amount of high water absorption resin in comparative example 1 is too small, which makes the amount of saturated resin formed after water absorption in comparative example 1 too small, and the number of thermal insulation cavities formed after the thermal insulation layer hardens and dries is also greatly reduced, so that the thermal insulation layer is more dense, the dry density increases, the compressive strength improves to a certain extent, but the thermal conductivity increases significantly, which is not conducive to the overall thermal insulation effect of the product; while the amount of high water absorption resin in comparative example 3 is too high, which leads to too much saturated resin after water absorption, and too many thermal insulation cavities after the thermal insulation layer hardens and dries, although the thermal conductivity is low, but from the overall point of view, the compressive strength is insufficient, which is not conducive to the overall strength performance of the product; while the amount of high water absorption resin in example 1 is appropriate, which forms a sufficient number of thermal insulation cavities, although the compressive strength is not as good as that of comparative example 1, but it is also better than the compressive strength of similar products on the market, and at the same time, it also maintains excellent thermal insulation effect.
[0074] (2) From Example 1 and Comparative Examples 2 and 4, it can be seen that the amount of hollow microspheres also has a significant impact on the performance of the product, especially on the flowability of the self-leveling and the dry compressive strength: in Comparative Example 2, the amount of hollow microspheres in the thermal insulation base is too high, and after the self-leveling slurry is poured on the thermal insulation layer, although it can quickly flow and the surface is flat, the strength of the entire self-leveling layer is affected, resulting in that the overall self-leveling layer is not strong enough after the thermal insulation material is completed, and under the action of a relatively high pressure, cracks appear on the surface of the product of Comparative Example 1; in Comparative Example 4, the amount of hollow microspheres in the thermal insulation base is too low, and after the self-leveling slurry is poured on the thermal insulation layer, the self-flowing speed is very slow, and the operator needs to repeatedly batch and scrape the entire self-leveling layer several times to make the flatness of the surface of the self-leveling layer meet the construction requirements, and if waiting for it to flow and level by itself, it cannot be achieved after the material solidifies; while in Example 1, after the self-leveling slurry is poured on the thermal insulation layer in actual construction, the slurry can quickly flow and spread on the thermal insulation layer in a short time, and the operator almost does not need to batch and scrape it several times, and only needs to batch and scrape it one or two times in some places to make the overall surface of the self-leveling layer meet the construction requirements, and more importantly, under the action of a relatively high pressure, the surface of the product of Example 1 is very complete and no cracks appear.
[0075] (3) From Example 1 and Comparative Example 5, it can be seen that the amount of hollow glass beads in the thermal insulation material of Comparative Example 5 is greatly reduced, which makes the dry density and thermal conductivity of the thermal insulation material of Comparative Example 5 significantly increase, although the increase of the dry density and the compressive strength is beneficial to the performance of the product, but considering the thermal insulation effect of the product, the increase of the thermal conductivity is relatively large, which also makes the equivalent thermal conductivity of the overall thermal insulation material increase greatly, and such adjustment is actually not conducive to the overall performance of the product.
[0076] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application and not to limit the technical solutions, and those of ordinary skill in the art should understand that those who modify or equivalently replace the technical solutions of the present application without departing from the spirit and scope of the technical solutions should be covered in the scope of the claims of the present application.
Claims
1. A floor insulation material, characterized by The floor thermal insulation material comprises, from top to bottom, a hollow gel gypsum self-leveling layer, a hollow gel gypsum thermal insulation layer and an interface layer; the interface layer is made of a hollow gel gypsum thermal insulation base material; the hollow gel gypsum thermal insulation layer is made of a hollow gel gypsum thermal insulation base material and a foaming agent; and the hollow gel gypsum self-leveling layer is made of a hollow gel gypsum self-leveling material. The hollow gel gypsum thermal insulation base material comprises, by weight, 80-90 parts of gypsum powder, 1-3 parts of superabsorbent resin, 0.1-0.2 parts of water reducing agent, 4-5.7 parts of hollow microspheres, 0.5-1 part of silica fume and 0.05-0.1 part of modifier, and acceptable range of water. The hollow gel gypsum self-leveling material comprises, by weight, 65-75 parts of gypsum powder, 0.2-0.3 parts of water reducing agent, 4-8 parts of hollow microspheres, 0.03-0.05 parts of welan gum, 0.03-0.05 parts of cellulose ether, 0.02-0.05 parts of modifier, 0.03-0.05 parts of defoaming agent, 0.5-1.5 parts of metakaolin, 5-8 parts of cement, 7-25.19 parts of heavy calcium carbonate, and acceptable range of water. The gypsum powder is β-type hemihydrate gypsum; the water reducing agent is modified polycarboxylic acid water reducing agent; the modifier is one or both of sodium gluconate and lactose; and the hollow microspheres are one or both of hollow glass beads and expanded microspheres. The superabsorbent resin is one or both of starch grafted acrylamide and crosslinked carboxymethylcellulose grafted acrylamide; and the superabsorbent resin has a fineness of 600-800 mesh.
2. The floor insulation material according to claim 1, wherein The hollow gel gypsum thermal insulation base material further comprises 0-14.35 parts of light calcium carbonate, which is light calcium carbonate having a fineness of 300-400 mesh.
3. The floor insulation material according to claim 1, wherein In the hollow gel gypsum thermal insulation base material, the hollow microspheres have a fineness of 200-300 mesh; and in the hollow gel gypsum self-leveling material, the hollow microspheres have a fineness of 60-80 mesh.
4. The floor insulation material according to claim 1, wherein The welan gum has a fineness of 300-400 mesh; and the cellulose ether has a viscosity of 1000-2000 mpa·s.
5. The floor insulation material according to claim 1, wherein The metakaolin has a fineness of 1000-1500 mesh; the cement is P·O42.5; and the heavy calcium carbonate has a fineness of 200-300 mesh.
6. The floor insulation material according to claim 1, wherein The foaming agent comprises, by weight, 20-40 parts of tea saponin, 4-8 parts of polyvinyl alcohol, 5-10 parts of acrylic emulsion and 42-71 parts of water.
7. The floor insulation material according to claim 6, wherein The polyvinyl alcohol has a fineness of 160-200 mesh; and the acrylic emulsion has a glass transition temperature of 5-10℃.
8. A method of installing a floor insulation material, characterised in that, The construction method comprises the following steps: Step 1: Sprinkle water on the surface to be constructed to wet the surface until the surface is saturated with water; Step 2: When there is a small amount of liquid water on the surface to be constructed, sprinkle the hollow gel gypsum thermal insulation base material, rub the hollow gel gypsum thermal insulation base material into a slurry with a brush, and then perform interface treatment on the surface to form an interface layer; and Step 3: dilute the foaming agent with water, and make it into foam with a foaming machine for standby; wherein, the amount of water is 40 times of the amount of foaming agent; Step 4: add water into the mixer, then add the hollow gel gypsum thermal insulation base material and stir until uniform, then pour the foam into the mixer and continue to stir to obtain the hollow gel gypsum thermal insulation slurry; Step 5: pour the hollow gel gypsum thermal insulation slurry obtained in step 4 on the surface of the interface layer, and pour to the required thickness, and after hardening, the hollow gel gypsum thermal insulation layer is formed; Step 6: after the hollow gel gypsum thermal insulation layer is completed, pour the self-leveling slurry made of self-leveling material on the hollow gel gypsum thermal insulation layer, and batch and scrape to the required thickness to form the hollow gel gypsum self-leveling layer.
Citation Information
Patent Citations
Weak water absorption interface complete gelation brushing and anti-hollowness construction method
CN101560818A
Processing method of fly ash cement foam solid board
CN102491708A
Hydraulic composition with prolonged open time
CN105209404A
High-wear-resistant resin floorboard
CN106313646A
Gypsum-based self-leveling material
CN110015880A